A Primeron the IMF's Information Notice System - Desruelle, Dominique (IMF Working Papers; Working Paper ;, 1997)
This paper describes the methodology and the data used to compute nominal and real effective exchange rate indices in the International Monetary Fund's Information Notice System (INS). In particular, it highlights improvements to the INS implemented over 1994-96, including modifications to the computational methodology, use of updated data, and extension of the INS to recent Fund members.